(The Use of Organic Acid and Thermal Adequacy on the Canned String Beans) - Timur Antara, Ngakan; G. Pohan, H; -, Subagja (Balai Besar Industri Agro, 2001)
Research on the canned string beans has been conducted .the formulation used was 1% salt,the organic acid (0.27% citric acid and 0.22% lastic acid ) and types of packaging (timplate and retort pouch) the product were stored for 0,2,4 and weeks the results showed that the result showed that the effect of storage gave the decrease of PH ,protein ,vitamin c and hardness.the microbial contents were relatively unchanged during storage .the process time required for tinplate retort pouch were 0.057 minutes respectively ,which adequate to render to canned string beans (pH< 4.5) microbiologically safe .